Вплив особистості керівника на формування привабливої організаційної культури навчального закладу - Лепська, Ірина (Видавництво Національного університету "Львівська політехніка", 2009)
In the article the features of organizational culture of educational establishment and administrative activity of leader are examined as a leading factor which determines the process of forming of attractive organizational culture.